A modified Delphi study to identify strategies to promote health literacy in parents of children with cancer - Somaye Sayahi; Masoud Bahrami; Ahmad Ali Eslami; Alireza Moafi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Parents play a key role in the care, monitoring, management of symptoms experienced in children with cancer, the support, and follow-up of treatment. However, there is a paucity of research as how to improve the health literacy of parents with cancer. The aim of this study was to identify the best and most important strategies to promote health literacy in parents of children with cancer. MATERIALS AND METHODS: A two-step modified Delphi method was used to establish consensus in Iran in 2021. Fourteen experts representing oncology, clinical nursing, and faculty members of nursing were selected by purposive sampling. In round one, 90 strategies to promote health literacy obtained in the qualitative study were distributed to the experts, which were scored from 1 to 5. In order to discuss statements without consensus in the first round, round two was held in a face-to-face meeting. Descriptive statistics such as mean, standard deviation, and percentage of response frequency were used to calculate agreement levels between experts. RESULTS: In round one, 57 statements reached a consensus. In round two, 21 statements reached a consensus. Finally, 78 statements reached consensus representing four domains including functional health literacy, interactive health literacy, critical health literacy, and care health literacy. CONCLUSION: Delphi method helps to identify the best and most important strategies to use in health literacy promotion programs for parents of children with cancer. Identifying these strategies will help health officials, planners, and policymakers.